(untitled) (ACME, 2021)
Felice Cavallotti’s theatrical activity has often been considered an episodic result of an eclectic intelligence, but still mainly devoted to politics and social commitment. Among the biographers and scholars who have dealt with Cavallotti, few have realized the constant interest and assiduous work carried out by the author for the scenes, often reproducing inaccurate and second-hand judgments and analyzing in a synthetic way their vast dramaturgical work. Little known, in fact, is also the political activity carried out by Cavallotti for the theater (which finds expression in the draft reform of the law of 1875 on copyright) his constant relationships with company administrators, managers and actors, documented by a rich correspondence preserved at the Giangiacomo Feltrinelli Foundation offers the opportunity to reconstruct more closely a significant moment of Italian theatrical life in the second half of the nineteenth century.